Utilization of Economic Potential of Lantana camara - Soni, P. L.; Naithani, Sanjay; Gupta, P. K.; Bhatt, Amit; Khullar, Ritu (Indian Forester, 2006)
Utilization of Lantana camara can be an effective method for managing the weed. It is of potential economic value as it contains appreciable quantity of cellulosic fibres, have excellent strength properties, but till date not been exploited commercially. Owing to the presence of fibres, L. camara has potential to be utilized for making value added products such as α- cellulose and its derivatives, hand made paper, wood composites (which are good substitute of solid wood depending upon the end use) and furniture. Preliminary studies conducted have shown that Lantana camara contains ∼66 % holocellulose and ∼27% lignin. The average fibre length is 912μ with fibre diameter ∼22μ. α-Cellulose was isolated from L. camara with product yield ∼40%, brightness ∼80% at ∼95% purity having negligible ash content. α-Cellulose isolated from L. camara was derivatized to prepare water soluble carboxymethyl cellulose (CMC) having DS of 1.22, viscosity 600 cps (1% solution) and 7500 cps (2% solution).